Instructor Maladaptive and Adaptive Relational Styles (I-MARS) as drivers of online-student retention and satisfaction - Stamatis Elntib (Computers and Education Open)
This study retrospectively assessed forum and module-based email communications between instructors and students. The data set analysed consisted of 40.000 forum posts and 10.000 Blackboard emails matched with 522 end of module student surveys extracted from 57 asynchronous and 100 % online postgraduate modules. Using structural equation modelling, it was demonstrated that adaptive and maladaptive instructor interpersonal behaviors were inversely related. Student retention during the first two weeks was positively associated with instructor adaptive and maladaptive (mainly passive) forum behaviors and negatively associated with instructor disengagement from the forum discussions. Student retention from week 3 onwards was positively associated with adaptive forum and email instructor communication and with instructor active attempts to embrace student autonomy but was negatively associated with instructor empathy. Maladaptive email instructor behavior negatively predicted student-satisfaction. Diagnosing and mapping the archetypal relational styles instructors use to engage with students may allow a better understanding of the interpersonal dynamics of online student retention and satisfaction.